Usage of the V. Dahl’s linguocultural diversity in the process of teaching Russian language to foreign students at the initial stage - Салахатдінова, Е.; Юган, Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
The article describes the main directions of linguistic work in the process of teaching Russian as a foreign language on the basis of V. Dahl’s linguistic and cultural dichology. At the present time, “The Explanatory Dictionary of the Great Living Russian Language” and “Proverbs of the Russian People” remain the most important scientific lexicographic and folklore by the means of enriching the lexical reserve of foreign students, as well as enriching their spiritual and moral education and the development of personal creative potential.In Russian as a foreign language classes at level A 1, as exercises in phonetics and for pronunciation, we offer tongue twisters from the collection of V. Dahl’s proverbs, and folklore texts are given without semantization.Paremiological material is used during the study of grammatical topics (as illustrative material) and for the development of students' speech. The use of proverbs and sayings during the Russian language classes contributes to the development of students' language intuition, helps to develop a serious and responsible attitude to the word, not only as a means of communication but also as a complex mechanism of influence on the listener, on his mental state. The linguistic personality, along with mastering the lexical minimum, the development of skills and abilities to use lexical material following the grammatical and syntactic structures of the language, masters the concepts of the culture of another society. Systematic work with paremias expands the lexical reserve of foreigners, revives their speech.Appeal to the Explanatory Dictionary by V. Dahl is associated with the work on nonequivalent vocabulary in the course of literature. The teacher’s choice of vocabulary volume, illustrative material, and principles of adaptation of the Dahl’s vocabulary “nest” for use in classes with foreigners in each case depends on the level of the group, the plan of the leson and the time allotted by the teacher to work with lexical material and lexicographic works.